Fear of Missing Out and Physical Activity in the Digital Age: A Bibliometric Analysis - Nur Fadly Alamsyah; Ririn Mamiek Wulandari (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to map the development of research on Fear of Missing Out (FOMO) and physical activity in the digital era using a Scopus-based bibliometric approach. Data were collected on August 13, 2025, covering publications from 2014–2025 using search queries combining FOMO, physical activity, and social media. From 113 initial documents, 92 peer-reviewed journal articles met the inclusion criteria. Analysis was conducted using Bibliometrix (R) and VOSviewer to identify publication trends, most productive journals, leading authors and countries, and thematic structures based on keyword co-occurrence. The findings indicate a steady growth trend with an average annual growth rate of 8.01%, peaking in 2023. Scientific production is dominated by developed countries such as the United States, Australia, and the United Kingdom. Thematic mapping reveals a shift from conceptual discussions on social comparison and digital anxiety toward technology-based interventions, including fitness applications, gamification, and virtual communities. The findings confirm the ambivalent role of FOMO as both a motivational driver and a potential psychological stressor. This study provides a conceptual foundation and future research directions for designing contextual and ethical digital fitness interventions. Keywords: Fear of Missing Out, physical activity, bibliometric analysis